(untitled) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Premessa - 2. La disciplina dell’esercizio della fede nei penitenziari inglesi - 3. La diversità delle fedi in carcere e il ruolo delle community chaplaincies - 4. Il carcere come spazio multi-religioso e i nodi irrisolti dall’Equality Act del 2010 - 5. La discriminazione per motivi religiosi nella giurisprudenza inglese e gli obblighi di prestazione a carico della pubblica amministrazione. Freedom of worship and Religious Diversity in English Prisons ABSTRACT: This article aims to highlight different aspects of the practice of faith in the British prison system. While the 1952 Prison Act gave a preeminent position to the chaplains of the Church of England, in the last decades multi-faith spaces of worship and spiritual-care groups have multiplied. Furthermore, ‘community chaplaincies’ and volunteers are active players in rehabilitation programs, especially in preventing recidivism, which is higher among ethnic and religious minorities. Both the Human Rights Act of 1998 and the Equality Act of 2010 have contributed to promote an ‘inclusive’ approach to religion pluralism, granting access to spiritual assistance and equal treatment among prison inmates. However, it is worth to consider if a State-centred management of religious diversity is a sustainable choice before the growing judicial litigation related to prisoners’ freedom of worship.